Editing metacaspase (StMC7) gene enhances late blight resistance in Russet Burbank potato - Bikram Poudel; Atul Sathe; Jacqueline C. Bede; Ajjamada C. Kushalappa (PLoS ONE, 2025)
Plants induce hypersensitive response programmed cell death (HR-PCD), upon biotrophic pathogen infection, to contain the pathogen to the point of infection. Apoptotic-like PCD (AL-PCD) has been reported upon prolonged hemibiotrophic and necrotrophic pathogen infection in potato, to feed on the dead cells for their growth. In potato, silencing of the gene StHRC lead to the suppression of AL-PCD, thus increasing resistance to blights in potato. This was also associated with a significant reduction in the expression of the metacaspase gene StMC7. Accordingly, the gene StMC7 was silenced in potato cultivar ‘Russet Burbank’ using CRISPR-Cas9 to improve disease resistance against late blight of potato caused by Phytophthora infestans. Following pathogen infection, the disease severity, pathogen biomass and StMC7 gene expression was lower in Stmc7 mutants as compared to wild type. Disease severity was also decreased in Alternaria solani inoculated Stmc7 mutants, compared to the wild type, suggesting possible multiple disease resistance in the Stmc7 knockdown mutants. This confirms that the silencing of StMC7 improves late blight disease resistance in potato.